JUDICIAL ANALYSIS ON THE POSITION OF LEGAL OPINION (FATWA) OF INDONESIAN COUNCIL OF ULAMA’ (MUI) IN STATUTORY REGULATION SYSTEM OF INDONESIA - Pofrizal Pofrizal; Akhmad Muslih; Ardilafiza Ardilafiza (Universitas Bengkulu, 2021)
The purpose of this research is to investigate, understand, describe, analyze and get a picture of the legal position of MUI fatwas in the statutory regulation system in Indonesia based on Law No. 12 of 2011 on Making Rules and Hierarchy of Rules. The method used in this research is normative. The results show that MUI fatwas are not included in positive law and don't have permanent legal power based on Law No. 15 of 2019 on the Amendment to Law Number 12 of 2011 on Making Rules and Hierarchy of Rules, so it cannot be legally applied to all Indonesian people. Also, fatwas of MUI cannot be a legal instrument to enforce legal act or to become the basis for imposing criminal sanctions for those who violate the law. It can only become positive law if the substance is stipulated by the authorized state institutions into laws and regulations as it is outlined in Law No. 15 of 2019 on the Amendment to Law No.12 of 2011 on Making Rules and Hierarchy of Rules.